Analsisis Pengaruh Merger dan Akuisisi Terhadap Kinerja Perusahaan Publik di Indonesia - Payamta Payamta; Doddy Setiawan (The Indonesian Journal of Accounting Research, 2013)
This research aims to examine the effect of merger and acquisition on firms’ performance at Jakarta Stock Exchange. Firm performance is measured using financial ratios: current ratio, quick ratio, total assets to debt ratio, net worth to debt ratio, total assets turnover, fixed asset turnover, ROI, ROE, NPM and OPM and abnormal return around Mergers and Acquisition (M&A) announcement date. Sample of this research consists of 16 manufacturing firms from 1990-1996. We use wilcoxon sign test and manova for research analysis. The results from manova test shows that financial ratios simultaneously indifference between before and after M&A. Abnormal return after M&A announcement date significantly different from abnormal return before M&A announcement date.  Investor earned positive abnormal return at before M&A announcement and turn to negative abnormal return after M&A announcement. Partial test using wilcoxon sign test shows that total asset turnover, ROI, ROE at 1 years before and 1 years after M&A announcement, total asset turnover and fixed asset turnover at 2 years before and 1 years after M&A, total asset turnover, fixed asset turnover, ROI, ROE and NPM at 1 years before and 2 years after M&A, total asset to debt, net worth to debt, total asset turnover and fixed asset turnover at 2 years before and 2 years after M&A are significantly different. These financial ratio getting worse after M&A. These results indicated that M&A does not provide sinergy for firms and they can not achieve economic motive.